Hinged tarsal flap: A novel technique for canthal tendon reconstruction. Issue 1 (January 2023) - Awad, Mary; Wilde, Craig; Tambe, Katya
Background/Objectives: Reconstruction of the medial canthal region is challenging due to the complex regional anatomy. Options to reconstruct a medial canthal tendon sacrificed during tumour removal is limited. We present a novel surgical technique where hinged tarsal flap serves to substitute the canthal tendons. Methods: This is a retrospective consecutive case series of five patients that underwent canthal reconstruction using this novel technique between May and December 2020. Electronic patient records and medical photograph database were reviewed. Patient demographics, co-morbidities, location and histology of the lesion, size of the resultant defect, reconstructive technique and post-operative complications were noted. Results: All patients had good eyelid stability with no malposition, lagophthalmos or exposure keratopathy. No or minimal distraction of the eyelid from the globe, good cosmetic outcomes and no troublesome watering was reported. No wound dehiscence, no sight loss and no further surgical intervention was warranted. Conclusion: Multiple techniques have previously been described to reattach the medial canthal tendon with silk or supramid sutures. Transnasal wiring, stainless-steel screw and mini-plate fixation are also described, but carry a high risk of complications and are unfamiliar amongst most oculoplastic surgeons. Our technique is quick and simple and utilises autogenous tissue without breaching the periosteum which acts as a natural barrier to tumour infiltration. Refashioning the canthal tendon aids to lengthen the remaining eyelid stump, reducing the horizontal length required to reform the newly constructed eyelid and facilitates the reconstruction.